1961
DOI: 10.1152/ajplegacy.1961.201.1.97
|View full text |Cite
|
Sign up to set email alerts
|

Distensibility of the dog left ventricle

Abstract: Left ventricular diastolic pressure-circumference curves were determined in 13 dogs, during stepwise hemorrhage and transfusion of blood. The linearity and small amount of scatter in the pressure-circumference curves obtained during control circumstances is evidence that elasticity rather than viscosity or inertia is the dominant determinant of the curve. Coincident with the slow infusion of epinephrine the distensibility increased. The importance of viscosity and inertial effects in the myocardial wall may al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
20
2

Year Published

1962
1962
1994
1994

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(23 citation statements)
references
References 0 publications
1
20
2
Order By: Relevance
“…Variations in heart rate have been demonstrated to alter ventricular end-diastolic compliance (Braunwald et al, 1960), but in our study, heart rate did not change during CPPV. CPPV may alter neurohumoral stimuli, but evidence indicates that changes in circulating catecholamines and autonomic discharge to the heart do not decrease ventricular end-diastolic compliance (Wiggers, 1927;Mitchell et al, 1960;Hefner et al, 1961;Wildenthal et al, 1969a;Wildenthal et al, 1969b). Changes in coronary perfusion pressure or coronary blood flow can alter ventricular end-diastolic compliance (Cross et al, 1961), but these variables did not change during CPPV in our study.…”
Section: Discussioncontrasting
confidence: 60%
“…Variations in heart rate have been demonstrated to alter ventricular end-diastolic compliance (Braunwald et al, 1960), but in our study, heart rate did not change during CPPV. CPPV may alter neurohumoral stimuli, but evidence indicates that changes in circulating catecholamines and autonomic discharge to the heart do not decrease ventricular end-diastolic compliance (Wiggers, 1927;Mitchell et al, 1960;Hefner et al, 1961;Wildenthal et al, 1969a;Wildenthal et al, 1969b). Changes in coronary perfusion pressure or coronary blood flow can alter ventricular end-diastolic compliance (Cross et al, 1961), but these variables did not change during CPPV in our study.…”
Section: Discussioncontrasting
confidence: 60%
“…Such an element might be "passive" or might represent the degree of Circulation Research, Vol. XXIII, August 1968 persistent interaction in the contractile element. Other types of studies have suggested that the contractile element has viscous properties (8).…”
Section: Discussionmentioning
confidence: 99%
“…• During the past forty years a variety of considerations have suggested that the diastolic pressure-volume relationship for the mammalian ventricle might vary as a result of some change in the characteristics of the myocardium (1)(2)(3)(4)(5)(6)(7)(8). Moreover, it was recognized early that under appropriate conditions variability in the pressure-volume relationship would influence both the performance of the heart as well as any evaluation of performance which employed measurement of enddiastolic pressure as an index of fiber length.…”
mentioning
confidence: 99%
“…However, all of the studies have been performed in the condition with the pericardium removed. On the other hand, in acute volume overload, the pericardium protects the heart from overdistension and contributes to elevation of left ventricular diastolic pressure at any given volume through pericardial restraint (Hefner et al 1961; Spotnitz and Kaiser 1971;Glantz et al 1978 ; Shirato et al 1978Shirato et al , 1982Janicky and Weber 1980). Furthermore, previous study in our laboratory has shown that the pericardium modifies the end-systolic pressure-segment length relationship of canine left ventricle in acute volume overload (Kanazawa et al 1983).…”
mentioning
confidence: 83%